2022
DOI: 10.3389/fpsyg.2022.965998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of e-service quality on customer engagement behavior in community e-commerce

Abstract: Customer engagement behavior is a critical success factor for community e-commerce. While many community e-commerce websites are currently improving service quality to enhance customer engagement behavior, little is known about how such e-services affect customer engagement behavior. Building upon the stimulus-organism-response (SOR) model, this study developed a research model to explain how e-service quality of community e-commerce platform affects customer engagement behavior through customer trust and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…To test whether there is multicollinearity in our data, the variance inflation factor (VIF) was estimated. The results showed that the VIF values ranged from 1.758 to 2.270, which were less than the threshold of 3.33, indicating that there was no obvious multicollinearity among the variables ( Fan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 96%
“…To test whether there is multicollinearity in our data, the variance inflation factor (VIF) was estimated. The results showed that the VIF values ranged from 1.758 to 2.270, which were less than the threshold of 3.33, indicating that there was no obvious multicollinearity among the variables ( Fan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 96%
“…Basu et al (2022) validated that both online and offline dimensions of service quality positively promote customer green citizenship behaviors. Ullah et al (2018) and Fan et al (2022) believe that all dimensions of service‐experience quality enhance CE. The results of the different effects of the different dimensions of service experience in this study differ from those of Ullah et al (2018), Fan et al (2022), and Basu et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of sustainable consumption, service experience promotes CE in both online and offline industries (Basu et al, 2022). For online services, system design, safety guarantees, and interactive services have a positive impact on CE behavior (Fan et al, 2022). On the other hand, for offline services, product categories, store atmosphere, and interpersonal communication are closely related to CE behaviors (Mohd‐Ramly & Omar, 2017).…”
Section: Hypotheses and Theoretical Modelmentioning
confidence: 99%
“…Lin et al (2023) examined the user choice of e-commerce platform for buying organic food and continuous usage intentions by using demand, convenience, interactivity, playfulness on enjoyment and impulse buying behavior. Furthermore, Fan et al (2022) examined e-service quality of community e-commerce platforms including (system design, intelligent fulfilment, security assurance, interactive service) on trust, perceived risk and CE behavior. Nam et al (2020) used the stimulus–organism–response model to conduct a cross-cultural comparison of the impact of e-service quality on consumers’ trust-behavioral intentions in online apparel shopping.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Researchers have emphasized CE in e-commerce (Kennedyd et al , 2022; Fan et al , 2022; Vohra and Bhardwaj, 2019) keeping in view how consumers spend considerable time. According to Abdullah et al (2020), convenience, incentive offers, security and privacy, ease of use, and website reputation all impact e-commerce factors such as product or service information.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%